2021
DOI: 10.1002/ps.6748
|View full text |Cite
|
Sign up to set email alerts
|

Field and greenhouse application of an attract‐and‐kill formulation based on the yeast Hanseniaspora uvarum and the insecticide spinosad to control Drosophila suzukii in grapes

Abstract: BACKGROUND: The invasive insect Drosophila suzukii (Matsumura) is an important pest of several red grape varieties. The yeast Hanseniaspora uvarum (Niehaus), which is associated with D. suzukii, strongly attracts flies and stimulates them to feed on yeast-laden food. In the present study, a formulation based on H. uvarum culture with spinosad insecticide was applied to the foliage of vineyards and control of D. suzukii wascompared to applying spinosad to the whole plant. After successfulH. uvarum and insectici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…5, Online Resource 8). H. uvarum is one of the main yeast symbionts of berries, it is renowned for its ecological relations with D. suzukii and interferes with the behavior of the insect (Rehermann et al 2021;Spitaler et al 2022;Mori et al 2017;Jones et al 2021;Lewis and Hamby 2019;Hamby et al 2012). Although the compounds from H. uvarum headspace with activity on the DsuzOr69a-subunits were not identified, by invoking responses, it demonstrates involvements of DsuzOR69as in binding compounds emitted by this yeast, and it further remarks the ecological relations between this microorganism and the D. suzukii insect.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…5, Online Resource 8). H. uvarum is one of the main yeast symbionts of berries, it is renowned for its ecological relations with D. suzukii and interferes with the behavior of the insect (Rehermann et al 2021;Spitaler et al 2022;Mori et al 2017;Jones et al 2021;Lewis and Hamby 2019;Hamby et al 2012). Although the compounds from H. uvarum headspace with activity on the DsuzOr69a-subunits were not identified, by invoking responses, it demonstrates involvements of DsuzOR69as in binding compounds emitted by this yeast, and it further remarks the ecological relations between this microorganism and the D. suzukii insect.…”
Section: Discussionmentioning
confidence: 98%
“…Among the first studies on D. suzukii behavior, it was demonstrated that chemosensory information influences reproduction of the insect (Revadi et al 2015a). While possible frontiers in mating disruption still seem to be far, other methods based on D. suzukii chemical sensing demonstrated promising effects in the development of attract and kill control (Klick et al 2019;Rice et al 2017;Rehermann et al 2021;Spitaler et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Even the development of population control tactics including attracticides will benefit from the identification of highly specific SWD attractants ( Mori et al 2017 , Noble et al 2019 , Bianchi et al 2020 , Spitaler et al 2020 , Rehermann et al 2022 , Spitaler et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…13 For example, D. suzukii adults are attracted to fermentation odors 14,15 and other microbial volatiles. 16 Though fermentation volatiles are used as lures in the field, [17][18][19] effective repellents are also needed for successful push-pull management. Currently, 1-octen-3-ol, geosmin, and 2-pentylfuran have been identified as promising D. suzukii repellents.…”
Section: Introductionmentioning
confidence: 99%